2011
DOI: 10.1016/j.scr.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cell-conditioned medium improves cardiac function following myocardial infarction

Abstract: Recent studies suggest that the therapeutic effects of stem cell transplantation following myocardial infarction (MI) are mediated by paracrine factors. One of the main goals in the treatment of ischemic heart disease is to stimulate vascular repair mechanisms. Here, we sought to explore the therapeutic angiogenic potential of mesenchymal stem cell (MSC) secretions. Human MSC secretions were collected as conditioned medium (MSC-CM) using a clinically compliant protocol. Based on proteomic and pathway analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
277
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(296 citation statements)
references
References 31 publications
11
277
0
8
Order By: Relevance
“…Extensive studies have explored and demonstrated a chemotactic response of MSCs to the site of injury in animal models of cerebral ischemia, TBI and myocardial infarction, and a functional improvement has been observed in clinical studies. [45][46][47][48][49][50][51] Ringden et al 52 showed that MSCs were efficacious in the treatment of hemorrhagic cystitis after allogeneic HSCT, and suggested that MSCs can be used to reverse the toxicities caused by chemoradiotherapy. However, there is little evidence showing that clinical benefits are dependent on the differentiation to tissue or direct repair from infused MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have explored and demonstrated a chemotactic response of MSCs to the site of injury in animal models of cerebral ischemia, TBI and myocardial infarction, and a functional improvement has been observed in clinical studies. [45][46][47][48][49][50][51] Ringden et al 52 showed that MSCs were efficacious in the treatment of hemorrhagic cystitis after allogeneic HSCT, and suggested that MSCs can be used to reverse the toxicities caused by chemoradiotherapy. However, there is little evidence showing that clinical benefits are dependent on the differentiation to tissue or direct repair from infused MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is now believed that the transplanted cells do not take over the functions of the cells that were lost due to ischemia, but, rather, that they support the recipient's surviving cardiac muscle cells by paracrine signalling, stimulating the angiogenesis in the affected area and reducing the size of myocardial lesion. Indeed, it has been demonstrated that application of medium conditioned by human mesenchymal stem cells (not the cells) also improved the cardiac function in a pig model of myocardial infarction [63].…”
Section: Cardiomyocytes Produced By Differentiation Ofmentioning
confidence: 99%
“…However, it has been suggested that donor cells cannot reside in the heart for a long time after transplantation (9,16,21), and some studies reported a paracrine signaling mechanism by which the donor cells reduced cell apoptosis and fibrosis and increased vasculogenesis to repair the injury (8,35,36).…”
Section: Introductionmentioning
confidence: 99%